Connecting land. A transdisciplinary workshop to envision a nature-connecting human habitat - Giusti M; Wang W; Marriott T (Taylor and Francis Group, 2023)
The design of the human habitat can either promote or oppose healthy living, sustainable lifestyles, and the ability to value nature in people. The goal of this paper is to provide some insights to shape a transdisciplinary agenda for future human habitats that are socially and ecologically sustainable. This is what Connecting Land is. Through a planned workshop, 19 professionals from a variety of complementary backgrounds create a vision for Connecting Land and then discuss policy actions required to achieve such a vision. The produced vision highlights a physically and emotionally healthy community that celebrates local nature in their traditions and rituals. Nature experiences are next door and symbiosis with nature is the constant background of the inhabitants' habits. The policy actions emerging from the workshop suggest that achieving Connecting Land requires integrated policies that simultaneously address children's experience-based education, the elimination of physical barriers to nature access, and legal actions to establish the rights of natural elements. To this goal, synergies between the design of natural landscapes, children's education, and short and long-term people's wellbeing are worth further exploration in both academia and practice. Sustainable human habitats that promote a healthy and sustainable culture do not need to be utopian.